Comparison of 2 Fluid Ingress/Egress Systems for Canine Stifle Arthroscopy Using Computed Tomography. Issue 8 (1st April 2014) - Warnock, Jennifer J.; Nemanic, Sarah; O'Donnell, Matthew D.; Wiest, Jason E.
<x xml:space="preserve">Abstract</x> Objective To evaluate volume of extra‐articular fluid egress and complications associated with 2 fluid ingress/egress techniques for stifle arthroscopy. Study Design Ex vivo study. Study Subjects Canine cadavers (n = 14). Methods Four cadavers (8 stifles) were used to validate 3D computed tomographic (CT) methods to quantify stifle joint intra‐ and extra‐articular volumes of iodinated contrast medium. Ten canine cadavers (20 stifles) had preoperative CT, followed by stifle arthroscopy using a 10% solution of iodinated contrast enhanced ingress fluid delivered by pressure bag (2PB) or by arthroscopic peristaltic pump (3FP). All 3FP limbs had an additional fluid egress portal placed by cannula and obturator. Arthroscopy was limited to 20 minutes/joint. The volume of the contrast medium egress into the soft tissues was measured on postoperative 3D CT reconstructed images. Results Mean percentage of total ingress fluids administered that remained in the joint and extra‐articular tissues postoperatively was 8.8 ± 1.2% in 3FP and 33.2 ± 8% in 2PB (P = .014). Two 3FP joints had 4–5 mm egress obturator tracks on the proximal medial trochlear ridge. Two 2PB joints had severe joint collapse from extracapsular fluid precluding further examination. Intermittent visual blurring by joint fluid mixing or fat pad fragmentation/dissolution was noted in 2PB joints. Conclusions A superior technique was not identified: 2PB had greater egress fluid tissue accumulation, whereas 3FP had better viewing of intra‐articular structures with less tissue egress fluid accumulation; however, cartilage damage was induced with the egress obturator.